2000
DOI: 10.1504/ijbt.2000.000131
|View full text |Cite
|
Sign up to set email alerts
|

Unsound science? Transatlantic regulatory disputes over GM crops

Abstract: In the risk debate over genetically modified (GM) crops, Europe's regulatory delays have often been branded as 'political', i.e. not based on science. Yet the US slogan 'sound science' tends to conceal value-laden features of safety claims, their weak scientific basis, their normative framing and their socio-political influences. By contrast a 'precautionary approach' can more readily identify scientific unknowns to be investigated, while acknowledging the agricultural-environmental values which inform risk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Those changes were explicitly articulated by the European Parliament when replacing Directive 90/220 with Directive 2001/18. When evidence emerged in the USA in 1999 indicating that the cultivation of GM crops might adversely affect emblematic species such as the Monarch butterfly, the authorities widened the scope of their deliberations about the possible environmental effects of cultivating such crops (Losey et al, 1999;Jasanoff, 2000, Levidow andCarr, 2000).…”
Section: Illustrations Of the Co-evolutionary Modelmentioning
confidence: 99%
“…Those changes were explicitly articulated by the European Parliament when replacing Directive 90/220 with Directive 2001/18. When evidence emerged in the USA in 1999 indicating that the cultivation of GM crops might adversely affect emblematic species such as the Monarch butterfly, the authorities widened the scope of their deliberations about the possible environmental effects of cultivating such crops (Losey et al, 1999;Jasanoff, 2000, Levidow andCarr, 2000).…”
Section: Illustrations Of the Co-evolutionary Modelmentioning
confidence: 99%
“…Even in the United Kingdom, probably the most pro-biotech of European countries, popular opinion has forced supermarket chains to refuse to carry GM foods, and an inquiry commissioned by the government and a long consultative process with the general public has concluded that GM crops carry uncertain risks to the environment. The EU has already proven its willingness to reject WTO decisions where there is scientific uncertainty regarding the potential health effects of a product and strong public support for the continued moratorium (as, for example, in the case of bovine growth hormone, where the EU has accepted the imposition of countervailing sanctions against some of its exports to maintain the moratorium on BGH) (Levidow and Susan, 2000). The implementation of the Cartagena Protocol on Biosafety, the ''precautionary principle,'' which permits the regulation of GMOs in the context of scientific uncertainty regarding the risks of such organisms, only strengthens the EUÕs position.…”
Section: Fighting Famine In Southern Africamentioning
confidence: 99%
“…An associated problem is to define the science required for such comparisons (Levidow and Carr, 2000). In case of GM crops it may be worthwhile to have the precautionary principle work both ways and require its application to the overall situation of potential costs and potential benefits (De Kathen, 1998;Goklany, 2000).…”
Section: Concepts For Ecological Risk Assessment: Familiarity and Thementioning
confidence: 99%
“…This may indicate that many of the concerns raised about GM crops reflect more the concerns about the changing nature of agriculture at large (Beringer, 2000), which draws on values and philosophical positions that are not readily changed upon the presentation of technical information. We acknowledge the prime importance of socio-economic and other issues for a proper technology assessment (Bruce and Bruce, 1998;EFB, 1999;NCB, 1999) and realise that prudent and transparent linking of science and politics may be the biggest challenge for the overall evaluation of GM crops (Levidow and Carr 2000). Despite this, we limit the scope of this review to the issues of plant science we consider to be most relevant.…”
Section: Introductionmentioning
confidence: 99%